2019
DOI: 10.3389/fnagi.2019.00021
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Mild Cognitive Impairment and Dementia in Parkinson’s Disease: The Parkinson’s Disease Cognitive Impairment Study

Abstract: Background: Cognitive impairment in Parkinson’s disease (PD) includes a spectrum varying from Mild Cognitive Impairment (PD-MCI) to PD Dementia (PDD). The main aim of the present study is to evaluate the incidence of PD-MCI, its rate of progression to dementia, and to identify demographic and clinical characteristics which predict cognitive impairment in PD patients.Methods: PD patients from a large hospital-based cohort who underwent at least two comprehensive neuropsychological evaluations were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 53 publications
7
79
0
Order By: Relevance
“…A total of 9 of 25 studies found that patients with PD‐MCI took higher LEDD than patients without PD‐MCI; our meta‐analysis confirmed this association (Supplementary Material 5; Table ), with a significant and positive ES (= 0.25). The heterogeneity among the studies was significant and moderate, but sensitivity analysis indicated stability of ES level, and there was no publication bias.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…A total of 9 of 25 studies found that patients with PD‐MCI took higher LEDD than patients without PD‐MCI; our meta‐analysis confirmed this association (Supplementary Material 5; Table ), with a significant and positive ES (= 0.25). The heterogeneity among the studies was significant and moderate, but sensitivity analysis indicated stability of ES level, and there was no publication bias.…”
Section: Resultssupporting
confidence: 71%
“…Of 21 studies, 8 revealed that PD‐MCI patients had higher H&Y stages than patients without PD‐MCI (Supplementary Material 5). Our meta‐analytic study showed that PD‐MCI patients had higher scores on the H&Y (Table ), with a significant and positive ES (= 0.33).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations